2006
DOI: 10.1557/proc-985-0985-nn05-02
|View full text |Cite
|
Sign up to set email alerts
|

Helium Migration Mechanisms in Polycrystalline Uranium Dioxide

Abstract: This study aims at identifying the release mechanisms of helium in uranium dioxide. Two sets of polycrystalline UO2 sintered samples presenting different microstructures were implanted with 3He ions at concentrations in the region of 0.1 at.%. Changes in helium concentrations were monitored using two Nuclear Reaction Analysis (NRA) techniques based on the 3He(d,α)1H reaction. 3He release is measured in-situ during sample annealing at temperatures ranging between 700°C and 1000°C. Accurate helium depth profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
2
5
0
Order By: Relevance
“…The depletion of this volume, not deeper than a few micrometres, could contribute to the driving force for the helium bulk release. An analogous phenomenon was observed by Martin et al [31,32] at the UO 2 grain boundary, during an annealing experiment performed on 3 He-implanted samples. The main release occurs between 1200 and 1600 K (area B in Figure 5).…”
Section: Helium Desorption From Infused Uo 2 Single Crystalsupporting
confidence: 81%
See 1 more Smart Citation
“…The depletion of this volume, not deeper than a few micrometres, could contribute to the driving force for the helium bulk release. An analogous phenomenon was observed by Martin et al [31,32] at the UO 2 grain boundary, during an annealing experiment performed on 3 He-implanted samples. The main release occurs between 1200 and 1600 K (area B in Figure 5).…”
Section: Helium Desorption From Infused Uo 2 Single Crystalsupporting
confidence: 81%
“…It is attributed to helium located in energetically favourable positions namely in the octahedral interstitial sites (OIS), i.e. the cavities in the middle of the oxygen cubes of the UO 2 lattice [32][33][34][35]. From these positions helium atoms diffuse to the surface via oxygen vacancy diffusion.…”
Section: Helium Desorption From Infused Uo 2 Single Crystalmentioning
confidence: 99%
“…An analogue phenomenon was observed by Martin et al [9,10] at the UO 2 grain boundary, during an annealing experiment performed on 3 He-implanted samples.…”
Section: Helium Release From Uo 2 Single Crystalsupporting
confidence: 67%
“…It has indeed previously been shown that above 1000°C, most of the trapped helium atoms are thermally re-soluted into the oxide matrix [1,9]. The gas should therefore be able to migrate above this temperature which would either induce its release or its capture by existing bubbles.…”
Section: Discussionmentioning
confidence: 97%